Exploring antibacterial and cytotoxic potential of endophytic Streptomyces isolated from the medicinal plant Litsea cubeba (Lour.) Pers: Endophytic Streptomyces from tLitsea cubeba - Quach Ngoc Tung; Vu, Thi-Hanh-Nguyen; Nguyen Thi Thu An; Bui Thi Lien; Le Thi Thanh Xuan; Phi, Quyet-Tien (Vietnam Journal of Science and Technology, 2022)
In the past decades, researchers and scientists have paid increasing attention to discover novel antibiotics and anticancer agents in combating infection and cancer diseases. It is believed that endophytic actinomycetes from medicinal plants provide a resourful niches for new compounds with significant bioactive properties. In the present study, we for the first time assessed antibacterial and cytotoxic activities of endophytic actinomycetes associated with Litsea cubeba (Lour.) Pers. A total of 25 endophytic actinomycetes were isolated from Litsea cubeba (Lour.) Pers collected at Lai Chau province, Vietnam, with the maximum number of isolates obtained from roots (44.4%), followed by stems (35.5%), and leaves (20.1%). Among them, 3 isolates LCL08, LCL25, LCL28 showed broad spectrum antibacterial activity against six pathogenic bacteria, which were subsequently identified as Streptomyces albogriseolus LCL08, S. olivaceus LCL25, and S. cavourensis LCL28 by using 16S rRNA sequence analysis. This is the first report of S. alborgriseolus isolated as endophyte. Ethyl acetate extracts from 3 strains exhibited strong antibacterial activity against 6 tested pathogens with the minimum inhibitory concentration value ranging from 2-64 μg/ml. Moreover, these extracts showed remarkable cytotoxic effects against Hep3B human hepatoma, MCF-7 breast cancer, and A549 lung cancer cell lines with the recorded viability of tested cancer cells ranging from 13.87 to 65.69%. These findings suggest that Streptomyces spp. recovered from Litsea cubeba (Lour.) Pers are an excellent source of natural antibacterial and cancer compounds that could be promising for further research.